Maqasid Syariah dan Kesetaraan Hak Perempuan - Safrida Ramadhania (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
Gender equality in Islamic communities continues to encounter substantial obstacles stemming from the prevalence of traditional fiqh interpretations that are often patriarchal in nature. In contrast, the maqasid syariah, which represents the overarching goals of Islamic law, underscores the importance of justice, public welfare, and human rights protection, encompassing the rights of women as well. This research seeks to investigate the relevance of maqasid syariah in the reconstruction of fiqh to tackle gender disparities. Utilizing a qualitative method with a library research approach, the study analyzes both classical and contemporary literature. The results reveal that maqasid syariah, which includes the protection of faith, life, reason, progeny, and wealth, offers robust justification for upholding women's rights across multiple facets of life, including spirituality, education, family, and economic spheres. The thoughts of modern scholars like Jasser Auda, Amina Wadud, Hashim Kamali, Abdullahi An-Na'im, Musdah Mulia, and Fatima Mernissi highlight the importance of contextual exegesis, critical hermeneutics, and gender awareness in Islamic jurisprudence. Consequently, maqasid syariah can serve as both a philosophical foundation and a practical tool for developing Islamic law that is more inclusive, responsive, and equitable for women. This research underscores the necessity of reconstructing fiqh based on maqasid syariah, enabling Islam to truly embody its principle as a rahmatan lil 'alamin that ensures equal rights for everyone.